MODERN APPROACHES TO ENVIRONMENTAL PROTECTION: GLOBAL CHALLENGES, SCIENTIFIC ANALYSIS AND SUSTAINABLE SOLUTIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the 21st century, environmental protection has become one of the most urgent global priorities. Rapid industrialization, urban expansion, and excessive resource exploitation have intensified environmental degradation, resulting in severe ecological, economic, and social consequences. This article provides a comprehensive scientific analysis of air, soil, and water pollution, climate change, biodiversity loss, and the decline of environmental culture. It evaluates modern approaches—including green technologies, renewable energy, circular economy practices, and ecological education—and proposes evidence-based recommendations for enhancing environmental sustainability.